PENINGKATAN NILAI EKONOMI PADA RTM (Rumah Tangga Miskin) MELALUI PROGRAM BEKERJA KEMENTERIAN PERTANIAN - Supardi Rusdiana; Tike Sartika (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
Almost all communities in Salopa Sub district are trying to raise livestock from native chickens, because free-range chicken is a very important component for people's lives. The purpose of the paper is to find out the increase in economic value of (poor households) RTM through the work program of the Ministry of Agriculture, IAARD, Animal Research Institute. The study used a survey of 54 RTM/farmer fard Mandalahayu Village 27 RTM/farmer and Mandalawangi Village 27 RTM/farmer. Primary data and secondary data are analyzed descriptively, quantitatively and economically. The results showed that the income of RTM/farmer in Mandalahayu Village was IDR.2.480.000/period with B/C ratio of 1.08 and in the village of Mandalawangi as much IDR.2.510.000/period with B/C ratio of 1.10. It can be said that the effort to enlarge DOC of chicken in RTM is not economically feasible. But if for a side business, savings and time fillers, it can be said to be feasible, because chickens can be sold as a source of sudden needs for farmers. The program works by the Ministry of Agriculture, expected to alleviate poverty, carry out agricultural development harmonization, so that farmers' income increases and poverty rates continue to be reduced or reduced